PENGARUH PELAKSANAAN BEDSIDE HANDOVER TERHADAP KEPUASAN KINERJA PERAWAT DALAM PEMBERIAN ASUHAN KEPERAWATAN - Azmi Sulintya S; Lusi Herawati; Ratih Nurhayati; Satipa Fatimah; Astri Fajar; Ana Lestari (CV. Adiba Aisha Amira, 2025)
Background: Bedside handover is a bedside patient handoff method recommended to enhance information accuracy, care continuity, and patient safety. It may also influence nurses’ job satisfaction. Objective: This study aimed to investigate the impact of bedside handover on nurses’ job satisfaction at Mayapada Hospital Bogor. Methods: A quantitative, descriptive-analytic cross-sectional design was employed, involving 81 inpatient nurses selected via proportional sampling. Data were collected using a bedside handover audit form with 17 standard indicators from Mayapada Hospital Group and a Likert-scale-based nurse job satisfaction questionnaire. Chi-Square analysis was used to examine the relationship between variables. Results: Bedside handover was largely rated as good in July (34.7%) and August (57%), with moderate ratings of 43.4% (July) and 28.5% (August), and poor ratings of 21.7% and 14.2%, respectively. Nurses’ job satisfaction showed a similar trend, with “satisfied” ratings increasing from 34.7% (July) to 57.1% (August), “moderately satisfied” decreasing from 46.5% to 28.5%, and “dissatisfied” decreasing from 19.5% to 14.2%. The Chi-Square test revealed p = 0.000 (p < 0.05), indicating a significant association between bedside handover implementation and nurses’ job satisfaction. Conclusion: The implementation of bedside handover significantly affects nurses’ job satisfaction and is essential for improving communication quality and patient safety. Additional factors, including workload, managerial support, and personal motivation, may also contribute to nurses’ job satisfaction.